Evaluasi Program Pendidikan dalam Meningkatkan Kualitas Pembelajaran - Ulfatun Nazilah; Rusdiana Navlia (PT. Penerbit Tiga Mutiara, 2026)
Educational program evaluation is understood as a systematic process that functions to assess the level of goal attainment, implementation effectiveness, resource-use efficiency, relevance to stakeholder needs, and sustainability of educational programs. This article originates from the issue of the limited use of comprehensive evaluation as a basis for educational decision-making, which causes evaluation to be frequently perceived merely as the measurement of learning outcomes. The research problem focuses on how the concepts, functions, and models of educational program evaluation can be comprehensively and applicatively understood based on experts’ perspectives. This study elaborates the ideas of Ralph Tyler, Cronbach, and Stufflebeam, who emphasize evaluation as a provider of meaningful information, a means of identifying program strengths and weaknesses, and a foundation for continuous improvement. The research method employs a literature study by reviewing books, scientific articles, and relevant journals discussing educational evaluation. The findings indicate that evaluation serves a formative function for continuous quality improvement and a summative function as a form of public accountability, encompassing aspects of policy, curriculum, learning processes, learning outcomes, and educational resource management. Various evaluation models, such as CIPP, Provus, Stake, Kirkpatrick, and the Logical Model, are identified as systematic frameworks that are complementary and contextual for application according to program needs. The conclusion confirms that educational program evaluation plays a strategic role in improving learning quality through planned measurement processes, the provision of accurate feedback, and data-based program adjustments. The novelty of this study lies in its comprehensive synthesis of evaluation concepts, functions, and models, presented integratively as a conceptual–practical guide for policymakers and educational practitioners, positioning evaluation not merely as an administrative activity but as an instrument for sustainable educational quality development.